(untitled) (International journal of artificial intelligence, 2025)
This research examines how employee training programs impact job performance in automobile manufacturing plants. In a highly competitive industrial environment, training and development are vital tools for improving operational efficiency and workforce adaptability. This study evaluates how structured and ongoing training programs influence employees’ technical proficiency, work discipline, and responsiveness to technological advancements in manufacturing. The results reveal that well-designed training initiatives lead to notable improvements in productivity, work quality, and employee engagement. Moreover, aligning training with strategic organizational goals enhances innovation, reduces production errors, and promotes cohesive teamwork. Ultimately, investing in employee development not only boosts individual performance but also contributes to the sustainable growth and competitiveness of automotive manufacturing organizations.